Genetic Screening of LCA in Belgium: Predominance of CEP290 and Identification of Potential Modifier Alleles in AHI1 of CEP290-Related Phenotypes - Coppieters, F (2016)
Leber Congenital Amaurosis (LCA), the most severe inherited retinal dystrophy, is genetically heterogeneous, with 14 genes accounting for 70% of patients. Here, 91 LCA probands underwent LCA chip analysis and subsequent sequencing of 6 genes (CEP290, CRB1, RPE65, GUCY2D, AIPL1and CRX), revealing mutations in 69% of the cohort, with major involvement of CEP290 (30%). In addition, 11 patients with early-onset retinal dystrophy (EORD) and 13 patients with Senior-Loken syndrome (SLS), LCA-Joubert syndrome (LCA-JS) or cerebello-oculo-renal syndrome (CORS) were included. Exhaustive re-inspection of the overall phenotypes in our LCA cohort revealed novel insights mainly regarding the CEP290-related phenotype. The AHI1 gene was screened as a candidate modifier gene in three patients with the same CEP290 genotype but different neurological involvement. Interestingly, a heterozygous novel AHI1 mutation, p.Asn811Lys, was found in the most severely affected patient. Moreover, AHI1 screening in five other patients with CEP290-related disease and neurological involvement revealed a second novel missense variant, p.His758Pro, in one LCA patient with mild mental retardation and autism. These two AHI1 mutations might thus represent neurological modifiers of CEP290-related disease.